2020
DOI: 10.3847/1538-4357/ab765d
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Multiwavelength Observations of the TeV Blazar 1ES 1215+303: Extreme Shift of the Synchrotron Peak Frequency and Long-term Optical–Gamma-Ray Flux Increase

Abstract: Blazars are known for their variability on a wide range of timescales at all wavelengths. Most studies of TeV gamma-ray blazars focus on short timescales, especially during flares. With a decade of observations from the Fermi-LAT and VERITAS, we present an extensive study of the long-term multiwavelength radio-to-gamma-ray flux-density variability, with the addition of a couple of short-time radio-structure and optical polarization observations of the blazar 1ES 1215+303 (z=0.130), with a focus on its gamma-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…The longer the light curve, the more effectively the high-flux part of the flux distribution can be studied. Some previous studies that compared normal and lognormal distributions have excluded flaring intervals from the flux distribution so as not to overly favor the heavier-tailed lognormal distribution (e.g., Giebels & Degrange 2009;Valverde et al 2020). However, when only considering heavy-tailed distributions, these intervals should not be excluded.…”
Section: Applicability and Extensions Of The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The longer the light curve, the more effectively the high-flux part of the flux distribution can be studied. Some previous studies that compared normal and lognormal distributions have excluded flaring intervals from the flux distribution so as not to overly favor the heavier-tailed lognormal distribution (e.g., Giebels & Degrange 2009;Valverde et al 2020). However, when only considering heavy-tailed distributions, these intervals should not be excluded.…”
Section: Applicability and Extensions Of The Modelmentioning
confidence: 99%
“…These distributions are commonly modeled as a lognormal distribution, which can arise through the multiplicative combination of many independent events (Uttley et al 2005). Variability consistent with lognormality has been observed in many studies of blazars using data in multiple wave bands (e.g., Giebels & Degrange 2009;Kushwaha et al 2017;Valverde et al 2020;Acciari et al 2021;Bhatta 2021).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…operations by Valverde et al (2020). We checked the dates of these four episodes and did not find evidence for them in the HAWC data.…”
Section: Es 1215+303mentioning
confidence: 99%
“…Review AGN are quite possibly the largest, most luminous, extragalactic objects observed in the known universe. The FERMI-LAT collaboration has generated an extensive catalogue of AGN in the highenergy regime [1][2][3][4][5]. A number of probes and missions are dedicated to the multi-messenger aspects of observing these energetic objects with variable emission [6,7].…”
Section: Introductionmentioning
confidence: 99%